OPTIMIZED PRODUCTION OF CELLULASE USING FRUIT WASTE AND ITS APPLICATION IN BIOETHANOL PRODUCTION - ELSA CHERIAN; M. DHARMENDIRA KUMAR; G.BASKAR (International Journal of Pharma and Bio Sciences, 2015)
Cellulases are a group of hydrolytic enzymes capable of degrading lignocellulosic materials into simpler sugar molecules. These enzymes are mainly produced by the microbial fermentation of bacteria and fungi. Usage of edible crops as substrates for the cellulase production may lead to a food crisis. So the present study mainly focuses on the production of cellulase by using apple waste as substrate with the help of previously isolated fungi Aspergillus fumigatus JCF. When apple waste was added with 1%cellulose as inducer a maximum yield of 2.20 IU/ml was obtained. Further, environmental and cultural conditions for the production of cellulase were optimized. A maximum cellulase activity of 2.28IU/ml was obtained at optimized conditions of 20% apple waste, 0.3% ammonium sulphate, 6.2 pH and five days fermentation period. Cellulase thus produced was used for bioethanol production. Biofuel production plays an important role in the current situation of increasing demand of fuel. Saccharified sample when inoculated with baker’s yeast yielded a maximum of 11.6gm/l of bioethanol.